Intravenous Bolus of Dexmedetomidine for Treatment of Severe Shivering After Caesarean Delivery Under Combined Spinal-Epidural Anaesthesia: A Randomized Dose-Response Study - Yang M; Li S; Drzymalski D; Chen X (Dove Medical Press, 2024)
Meijuan Yang,1,* ShuXi Li,1,* Dan Drzymalski,2 Xinzhong Chen1 1Department of Anaesthesia, Women's Hospital, Zhejiang University School of Medicine, Hangzhou, People's Republic of China; 2Department of Anaesthesiology and Perioperative Medicine, Tufts Medical Centre, Boston, MA, USA*These authors contributed equally to this workCorrespondence: Xinzhong Chen, Tel +86-571-87061501, Fax +86-571-87061878, Email chenxinz@zju.edu.cnPurpose: Shivering occurs frequently after caesarean delivery. The present study aimed to investigate the ED50 and ED95 of an intravenous (i.v.) bolus of dexmedetomidine for treating severe shivering after caesarean delivery under combined spinal-epidural anaesthesia.Patients and methods: Seventy-five parturients with severe shivering after caesarean delivery were randomized into one of the five groups to receive an i.v. bolus of 0.2 (Group D1), 0.25 (Group D2), 0.3 (Group D3), 0.35 (Group D4) or 0.4 (Group D5) μg/kg of dexmedetomidine. Effectiveness of shivering treatment was defined as a standardized shivering score decreasing to ≤ 1 within 10 min of dexmedetomidine injection. The ED50 and ED95 were determined by probit regression. Adverse effects were also compared among the groups.Results: The ED50 and ED95 of i.v. dexmedetomidine to treat severe shivering were 0.23 (95% CI, 0.16- 0.26) μg/kg and 0.39 (95% CI, 0.34- 0.52) μg/kg, respectively. No difference in the incidence of adverse effects was found between groups.Conclusion: An i.v. bolus of 0.39 μg/kg of dexmedetomidine will treat 95% of parturients experiencing severe shivering after caesarean delivery.Keywords: dexmedetomidine, shivering, caesarean delivery